The Impact of Regional Language Use on Student Interaction in Higher Education: Evidence from UIN Fatmawati Sukarno Bengkulu - Rina Novia Sari; Zana Hama Amin (JPI: Jurnal Pustaka Indonesia, 2024)
The use of regional languages in academic settings remains a complex sociolinguistic issue, as it can both foster cultural identity and influence the quality of student interaction in higher education. This study aimed to examine the effect of regional language use on classroom interaction among first-semester students in the Indonesian Language Education Program at Universitas Islam Negeri Fatmawati Sukarno Bengkulu. Using a quantitative quasi-experimental design with nonequivalent control groups, data were collected from 51 students through a validated questionnaire and analyzed using SPSS version 25, including normality, homogeneity, and paired-sample t-tests. The results indicated that the experimental group exposed to regional language integration in classroom discourse demonstrated significantly higher levels of interaction, confidence, and engagement compared to the control group using only standard Indonesian. These findings highlight that regional language use, when strategically integrated, enhances students’ participation and strengthens sociocultural bonds without undermining academic objectives. The implication of this research is that incorporating regional languages into higher education practices can serve as a valuable pedagogical strategy to enrich classroom interaction, promote multilingual competence, and support language policy development in multicultural academic contexts.